Thymoma exhibiting spontaneous regression with developing myasthenia gravis: A case report. Issue 10 (28th March 2022) - Nishina, Kazuhisa; Suzuki, Mikito; Nakamura, Azusa; Shimizu, Reiko; Shima, Toshiyuki; Harada, Masahiko; Hishima, Tsunekazu; Horio, Hirotoshi
Abstract: Spontaneous regression (SR) of thymoma is rare. A 44‐year‐old man with right chest pain underwent computed tomography (CT), which showed an 11.0 cm mass in the anterior mediastinum and right pleural effusion. He refused surgery and was sent home without medication and additional treatment. One year later, the mass had regressed to 5.5 cm, and the right pleural effusion had disappeared. He was then lost to follow‐up. Four years after the initial visit, he presented with diplopia and fatigue. A significant increase in his anti‐acetylcholine receptor antibody levels led to myasthenia gravis (MG) diagnosis. CT revealed a regressed mediastinal mass (3.0 cm). After extended thymectomy, histologic analysis confirmed a thymoma type B2, Masaoka stage IIa. The SR was due to intratumoral infarction. This report is the first to describe MG developing during SR. Anterior mediastinal tumors undergoing SR should be differentiated from thymomas and MG perioperative development should be considered. Abstract : We report a rare case of a thymoma undergoing spontaneous regression (SR) due to intratumoral infarction with myasthenia gravis (MG). This case demonstrates the natural course of SR of thymoma without any medication and treatment for 4 years. Anterior mediastinal tumors undergoing SR should be differentiated from thymomas and MG perioperative development should be considered.